Discharge characteristics of cathodic hollow-cathode plasma contactors and related similarity to ground simulations. (November 2019) - Xia, Qimeng; Xie, Kan; Wang, Ningfei
Abstract: This paper focuses on the main factors affecting the electron emission current–bias voltage ( I – V ) characteristics of cathodic hollow-cathode contactors and similarity conditions that should be satisfied in ground-based simulation experiments. These issues are of crucial importance for ensuring the reliability and credibility of the I – V data obtained in ground experiments, improving the I – V characteristics, and for reducing the mass flow consumption and dependence on the space environment. In this study, a 1-D spherically-symmetric model is first applied and compared with experimental data. We explore the influence of ion current, electron temperature, ion energy at the contactor exit, and environmental plasma density on the I – V curves, potential structure, and size of the plume area. The influence of the diameter of the vacuum chamber on the experimental I – V characteristics is investigated and the necessary conditions required for the diameter of the vacuum chamber is proposed. Moreover, an analysis is conducted of the effect of the background plasma source on the experimental I – V curves. The results suggest that the I – V behavior is sensitive to the exit ion current and flow rates. Another model is further employed to predict the exit ion-beam current for different net electron-emission currents and consumption flow rates at a given clamping current. The calculations show that a single-cathode contactor presents an extremely low utilization ratio. The exit ion current and utilization ratio should be effectively enhanced to improve the I – V characteristics. Highlights: Ion current and flow rate have great influence on the I-V curve of the plasma contactor. Large vacuum chamber can reduce the effect of boundary conditions on contactor working performance. The influence of environment plasma density is negligible when the flow rate is high.